2017
DOI: 10.1590/s1984-29612017036
|View full text |Cite
|
Sign up to set email alerts
|

Ticks infesting captive and free-roaming wild animal species at the São Paulo Zoo, São Paulo, Brazil

Abstract: Ticks are ectoparasites of worldwide distribution that affect vertebrates and can transmit pathogens to animals and humans. The Zoological Park Foundation of São Paulo (FPZSP) is located in a Conservation Unit in one of the most important remaining fragments of the Atlantic Rainforest biome in the suburbs of São Paulo, Brazil. The FPZSP houses more than 3,000 wild animals on exhibit, in breeding programs and in environmental education programs, and also attracts migratory birds and free-roaming wildlife. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…Our study found I. loricatus on D. aurita and D. albiventris as previously described in diverse Brazilian states such as Paraná, Rio Grande do Norte, São Paulo, and Pernambuco (21,(49)(50)(51). In the state of Pernambuco, I. loricatus was found infesting five marsupial species, including D. aurita and D. albiventris, with high infestation frequencies in these two marsupial species (50), similar to that observed in our study.…”
Section: Hosts and Ticks From Northeast Brazilian Rainforest Fragmentsupporting
confidence: 90%
“…Our study found I. loricatus on D. aurita and D. albiventris as previously described in diverse Brazilian states such as Paraná, Rio Grande do Norte, São Paulo, and Pernambuco (21,(49)(50)(51). In the state of Pernambuco, I. loricatus was found infesting five marsupial species, including D. aurita and D. albiventris, with high infestation frequencies in these two marsupial species (50), similar to that observed in our study.…”
Section: Hosts and Ticks From Northeast Brazilian Rainforest Fragmentsupporting
confidence: 90%
“…These studies are mostly concentrated in the Southeast region of the national territory, with the Sorocaba Zoo being the pioneer (TEIXEIRA et al, 2003(TEIXEIRA et al, , 2008(TEIXEIRA et al, , 2017MARTINS et al, 2015b;GONZALEZ et al, 2017). Other studies have been conducted in the South and Northeast regions of the Brazilian territory (BRUM & RICKES, 2003;DANTAS-TORRES et al, 2010a, 2010bPEREIRA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…No presente trabalho, foram ainda encontradas as espécies A. sculptum e A. aureolatum que são consideradas importantes vetoras da bactéria Rickettsia rickettsii agente etiológico da febre maculosa brasileira, tais encontros corroboram com outras pesquisas recentes desenvolvidas em Zoológicos no estado de São Paulo (MARTINS et al, 2015;GONZALEZ et al, 2017;TEIXEIRA et al, 2017).…”
Section: Resultsunclassified